Association of Short Antenatal Corticosteroid Administration-to-Birth Intervals With Survival and Morbidity Among Very Preterm Infants: Results From the EPICE Cohort. Issue 12 (December 2017) - Norman, Mikael; Piedvache, Aurelie; Børch, Klaus; Huusom, Lene Drasbek; Bonamy, Anna-Karin Edstedt; Howell, Elizabeth A.; Jarreau, Pierre-Henri; Maier, Rolf F.; Pryds, Ole; Toome, Liis; Varendi, Heili; Weber, Tom; et al.
Abstract : (Abstracted from JAMA Pediatr 2017;171(7):678–686) Prenatal administration of antenatal corticosteroids (ANSs) reduces neonatal morbidity and mortality in preterm infants and is recommended for women at risk of delivery before 34 weeks' gestation. There is consensus that neonatal benefits are maximized when ANSs are administered 24 hours to 7 days before delivery, but the latest point at which ANSs can be used effectively is unknown.